Home monitoring program for patients following cardiac surgery. (14th October 2021) - Sokolskaya, M; Shvartz, V A; Bockeria, O L; Bockeria, L A
Abstract: : Patient compliance with medical recommendations and monitoring of the cardiovascular system parameters after discharge from the hospital are important in the postoperative period. Material and methods: The program of remote home monitoring of patients after cardiac surgery was created and is used in clinical practice of the department of surgical treatment of interactive pathology. First of all, we analyzed the capabilities of apps for mobile phones, ECG monitoring devices, and blood pressure monitors with the ability to remotely reset data via Bluetooth which are available in Russia. In accordance with the requirements of the high-tech clinic, the following applications were selected: MediSafe (control of drug therapy), MedMBP (control of blood pressure), Ritmer (ECG monitoring), MiFit (a step tracker). In the follow-up program 25 patients (15 men, 10 women) were included. The average age is 59±11 years (min-29, max-91). Performed interventions: 7 patients underwent RFA, 6-valve replacement with a mechanical prosthesis, 2-valve replacement with a bioprosthesis, 7-CABG, 5-PCI. The patients gave their voluntary consent to participation, confirmed their readiness and ability to use apps and devices. The initial psychological status and the quality of life were assessed using the SF 36 and HADS questionnaires. All patients were given a tonometer for BP measuring, an ECG device and a step tracker to evaluate physical activity. According to the protocol, patients measure BP and ECG daily or additionally if they feel worse; using the mobile app, they note the taken medications. All data are sent to the server and analysis by the doctor. The doctor reviews the received indicators every day and, if necessary, contacts the patient to discuss treatment tactics. Results: For today the follow-up period is 3 months. During this period, 96% of patients strictly follow the program protocol. One patient has difficulties when using the ECG recorder, does not regularly follow the recommendations for drug therapy, which requires an individual approach. Based on the monitoring results, correction of antihypertensive therapy was necessary in 40% of cases, antiarrhythmic therapy-in 20%. In one case, a sinus node weakness syndrome was detected, and the patient was called to the hospital for the pacemaker implantation. Conclusion: The remote monitoring program is an effective and promising tool for monitoring patients after discharge from the hospital. It is clear that the results obtained from more patients and after a longer follow-up period would be more informative. However, the intermediate initial result indicates the necessity and effectiveness of this program. Funding Acknowledgement: Type of funding sources: None.